A review on therapeutic effects of Labisia pumila on female reproductive diseases - Zakaria, Alif Aiman; Mohd Noor, Mohd Hezmee; Ahmad, Hafandi; Abu Hassim, Hasliza; Mazlan, Mazlina; Ab Latip, Mohd Qayyum (Hindawi, 2021)
The Labisia pumila (LP) is a traditional plant that is locally known as Kacip Fatimah, Selusuh Fatimah, or Pokok Ringgang by the Malaysian indigenous people. It is believed to facilitate their childbirth, treating their postchild birth and menstrual irregularities. The water extract of LP has shown to contain bioactive compounds such as flavonoids, ascorbic acid, β-carotene, anthocyanin, and phenolic acid, which contribute extensive antioxidant, anti-inflammatory, antimicrobial, and antifungal. The LP ethanolic extract exhibits significant estrogenic effects on human endomentrial adenocarcinoma cell in estrogen-free basal medium and promoting an increase in secretion of alkaline phosphate. Water based has been used for many generations, and studies had reported that it could displace in binding the antibodies and increase the estradiol production making it similar to esterone and estradiol hormone. LP extract poses a potential and beneficial aspect in medical and cosmeceutical applications. This is mainly due to its phytoestrogen properties of the LP. However, there is a specific functionality in the application of LP extract, due to specific functional group in phytoconstituent of LP. Apart from that, the extraction solvent is important in preparing the LP extract as it poses some significant and mild side effects towards consuming the LP extracts. The current situation of women reproductive disease such as postmenopausal syndrome and polycystic ovary syndrome is increasing. Thus, it is important to find ways in alternative treatment for women reproductive disease that is less costly and low side effects. In conclusion, these studies proven that LP has the potential to be an alternative way in treating female reproductive related diseases such as in postmenopausal and polysystic ovarian syndrome women.